Pensar o espaço interior: materialização de ambientes em espaço teatral - Carla Sofia Rego Araújo (2018)
All architecture is born of the human necessity of a contained, enclosed and protected space, in which the human being can perform his activities and live. To project is, therefore, to organize a certain amount of space, convenient to a certain program, and to appropriate it for human use, in a given urban context established by local and surrounding characteristics. The volumetry and the external shape of the buildings, as a rule, condition the interior space and vice versa, being that scale, proportion, matter, light, and color, all merge together in the body of architecture. The way these elements relate and interact provokes the senses of the human being and influences his perception, characterizing the different situations experienced. This lead us to think of the interior space, in the sense of perceiving how its materiality guides either the architectonic thought and the way of projecting of the architects. In the search for case studies to reflect and ground these questions, among the various typologies of interior spaces, the theatrical was chosen because, as a privileged place of spectacle, culture and socialization, the theater is a space rich in different interiorities. From the scenography of narratives and main rooms, to the treatment of public and technical spaces around the spectator and the artist, the buildings destined to the theatrical practice possess a great variety of rhythms and forms in the design of the interior. Among the vast national patrimony, were selected theaters recently recovered and extended, in order to investigate how the dialogues between the past and the present manifest themselves, along with the project thinking, in the various characteristics that make the interior space. We were interested in analyzing and understanding how the choice of materials affects the architecture and its atmospheres, and reflect on the role of the architect in the creation of these particular environments.